Jawad Ali: A Historical Study of His Life, Works, and Methodology - Akab, Jassib AbdAlAmir; Karimipour, Hamid (Journal of Humanities & Social Sciences, 2025)
This research presents a historical study of the renowned Iraqi historian Jawad Ali, examining his life, scholarly writings, and methodological approach. Recognized as one of Iraq's first doctoral graduates from Germany, Jawad Ali pioneered a sophisticated and objective historical methodology. He rigorously prioritized original sources to ensure credibility and minimize personal bias within his extensive body of work.The study aims to: 1) explore Jawad Ali's biography, 2) analyze his most significant publications, evaluating their scholarly status and contribution, and 3) elucidate his distinctive historical methodology, opinions, and intellectual framework. Employing a historical research method, the investigation involved systematic collection, critical analysis, and interpretation of source material to ascertain historical accuracy and assess Jawad Ali's significance as a historian.Key findings establish that Jawad Ali secured a distinguished position within academic circles. This recognition stemmed not only from his seminal writings but also from his influential scholarly perspectives and ideas, which continue to benefit researchers. He established himself as a prominent Iraqi intellectual whose erudition significantly shaped subsequent generations of scholars and historical research in Iraq. Consequently, Jawad Ali emerges as a pivotal figure within the field of historical studies, particularly influencing Iraqi scholarship.
Keywords: Jawad Ali; Methodology; History; Iraq